The national campaign for regional museums: research and university between São Paulo and Belo Horizonte (Cadernos de Sociomuseologia, 2023)
In the 1960s, faced with numerous sociocultural transformations, but mostly, in the face of the Cold War and the implementation of the harsh military regime in Brazil, journalist Assis Chateaubriand, associated with figures such as Yolanda Penteado and Pietro Maria Bardi, led the National Campaign for Regional Museums, a patronage initiative, that with the support of the São Paulo Museum of Art, the journalistic group Diários Associados, as well as public authorities and other financiers, through the donation of initial new collections encouraged the opening of regional museums spread across Brazil.Starting from a dialogical methodology, this text seeks to reflect on some of the influences of the network and museum model implemented by the Campaign, through the different ways it dialogues with universities, and using as a case study the history of formation and donation of the Brasiliana Gallery collection to the Federal University of Minas Gerais.Keywords: Regional Museum; Regional Museums National Campaign; Brasiliana Gallery; Research; University.